Use of labour neuraxial analgesia according to maternal immigration status: a national cross-sectional retrospective population-based study in France. (December 2021) - Brebion, Myriam; Bonnet, Marie-Pierre; Sauvegrain, Priscille; Saurel-Cubizolles, Marie-Josèphe; Blondel, Béatrice; Deneux-Tharaux, Catherine; Azria, Elie; ,; Anselem, Olivia; Azria, Elie; Bonnet, Marie-Pierre; Cognet, Marguerite; et al.
Abstract: Background: Disparities in neuraxial analgesia use for childbirth by maternal origin have been reported in high-resource countries. We explored the association between maternal immigrant status (characterised separately by geographic continental origin and Human Development Index [HDI] of maternal country of birth) and neuraxial analgesia use. We hypothesised that immigrant women from low-resource countries may have more limited access to neuraxial analgesia than native French women. Methods: The study population, extracted from the 2016 National Perinatal Survey, a cross-sectional study of a representative sample of births in France, included only women who initially wished to deliver with neuraxial analgesia. We used multivariable multilevel logistic regression to explore the association between immigrant status and both use of neuraxial analgesia and its timely administration. Results: Among the 6070 women included, 88.1% gave birth with neuraxial analgesia and 15.8% were immigrants. There was no difference in neuraxial analgesia use between native French women and either immigrant women by geographic continental region of origin, or immigrants from countries with low HDI. However, immigrants from countries with very high HDI were more likely to give birth with neuraxial analgesia (adjusted odds ratio [aOR]=2.6; 95% confidence interval (CI), 1.2–5.8; P =0.018) and its timeliness <60 min after admission (aOR=1.8; 95% CI, 1.2–2.7; P =0.005) compared with native French women. Conclusions: In France, immigrant women from low-resource countries have similar access to labour neuraxial analgesia to native French women. Our results suggest differential neuraxial analgesia use in favour of immigrant women from very high HDI countries compared with native women.